Long-term functional outcomes of patients with very mild stroke: does a NIHSS score of 0 mean no disability? An interim analysis of the KOSCO study. Issue 9 (24th April 2017) - Chang, Won Hyuk; Sohn, Min Kyun; Lee, Jongmin; Kim, Deog Young; Lee, Sam-Gyu; Shin, Yong-Il; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; Han, Eun Young; Kim, Min Su; Jang, Shin Yi; et al.
Abstract: Purpose : To explore the long-term functional outcomes of stroke patients with very mild severity at 6 months after stroke. Methods : This study presents the interim results of the Korean Stroke Cohort for Functioning and Rehabilitation. On day 7, stroke evaluation was performed using the functional assessment battery including the National Institute of Health Stroke Scale (NIHSS). At 6 months after stroke, functional outcomes using the face-to-face functional assessment battery including Functional Independence Measure (FIM) were analyzed in the patients who had a score of 0 on the NIHSS at 7 days after stroke onset. Results : In the very mild stroke group, 455 patients were followed up at 6 months. Out of these patients, 11.0% had impairments in cognitive function, 14.1% had motor impairment, and 2.1% had impairments in their mobility measured by the functional assessment battery. At 6 months after onset, 3.3% of stroke survivors without recurrence showed dependency according to the FIM. Conclusions : Many acute stroke patients with mild stroke severity as assessed by the NIHSS had impairments in various functional domains, and could have been easily overlooked for intensive rehabilitation therapy. Candidates for comprehensive rehabilitation therapy might be better identified by the functional assessment battery. Implications for rehabilitation: Many acute stroke patients with mild stroke severity assessed by NIHSS could be easily overlooked for intensive rehabilitation therapy. Candidates for comprehensive rehabilitation therapy should be evaluated using a functional assessment battery rather than the NIHSS.